2010
DOI: 10.2169/internalmedicine.49.4211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low-Grade Inflammation on Plasma B-type Natriuretic Peptide Levels

Abstract: Objective B-type natriuretic peptide (BNP) is a cardiac hormone. The results of previous in vitro studies suggest that neurohumoral factors, and not only hemodynamic factors, may cause BNP secretion. In this study, we examined the impact of serum C-reactive protein (CRP) levels on the relationship between echocardiographic parameters and plasma BNP levels in patients with cardiovascular diseases. Methods and PatientsThe study population comprised 417 patients who visited our cardiovascular unit with a problem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The present study focused on patients with dyspnea who came to a tertiary emergency medical facility due to worsening of symptoms. Moreover, the inflammatory status was relatively high in the present population (Table 2), and inflammation has been previously reported to increase the plasma BNP levels (24). The severity of HF and the presence of inflammation may explain the higher cut-off values of the BNP levels in the present study, therefore the present findings are in line with the cut-off described in the JHFS statement.…”
Section: Cut-off Values In the Previous Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…The present study focused on patients with dyspnea who came to a tertiary emergency medical facility due to worsening of symptoms. Moreover, the inflammatory status was relatively high in the present population (Table 2), and inflammation has been previously reported to increase the plasma BNP levels (24). The severity of HF and the presence of inflammation may explain the higher cut-off values of the BNP levels in the present study, therefore the present findings are in line with the cut-off described in the JHFS statement.…”
Section: Cut-off Values In the Previous Studiessupporting
confidence: 88%
“…In the present study, many of the patients with respiratory disease had pneumonia and interstitial pneumonia, which causes BNP levels to rise, and this increase in BNP correlates with the level of CRP (23). Our previous report showed that inflammation increases the plasma BNP level (24). In septic patients, the severity of the illness is the main determinant of the BNP level, rather than cardiac function (25).…”
Section: Plasma Bnp Levels In Non-heart Failure Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…Caution must be exercised particularly for obese patients, because their plasma BNP levels can be low even in the presence of severe heart failure. Figure 6 shows an example of a clinical scenario using chest X-rays and the rapid BNP assay for the diagnosis of heart failure and other conditions (2,(12)(13)(14)22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study identified standard contributing factors affecting changes in plasma BNP levels. 15 Serial BNP measurements are useful in evaluating acute heart failure, and we attempted to investigate improvements in acute heart failure by assessing such measurements. 9 In terms of aging, no significant differences were observed in plasma BNP levels before treatment between older and younger age groups, suggesting that the degree of acute heart failure is not related to aging in the acute phase ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%